1994
DOI: 10.2535/ofaj1936.71.1_21
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Relationship between Saphenous Vein and Cutaneous Nerves

Abstract: Summary: The anatomical relationship between the saphenous veins and cutaneous nerves was investigated in 148 lower limbs of 74 cadavers in order to re-examine the stripping technique for treatment of varicose veins. The great saphenous vein frequently ran intimately along the saphenous nerve (59.5% in the middle third and 83.1% in the lower third of the leg) in the leg region. More than half of the latter cases showed an adhesive relationship in which the perineurium of the saphenous nerve was seen histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 5 publications
3
13
1
Order By: Relevance
“…Three further cadaveric studies (Murakami et al,1994; Dayan et al,2008 ; Veverková et al,2011) also described an adherence of the saphenous nerve to the great saphenous vein, by a common fascia at the distal part of the leg and the present study further supports this finding. The cadaveric study by Dayan and colleagues on 20 lower limb samples, found three consistent branches of the saphenous nerve during the course of travel through the leg (Dayan et al,2008).…”
Section: Discussionsupporting
confidence: 86%
“…Three further cadaveric studies (Murakami et al,1994; Dayan et al,2008 ; Veverková et al,2011) also described an adherence of the saphenous nerve to the great saphenous vein, by a common fascia at the distal part of the leg and the present study further supports this finding. The cadaveric study by Dayan and colleagues on 20 lower limb samples, found three consistent branches of the saphenous nerve during the course of travel through the leg (Dayan et al,2008).…”
Section: Discussionsupporting
confidence: 86%
“…This has been confirmed by developmental studies showing that superficial nerves guide the organization of vascular network (Mukouyama, Shin, Britsch, Taniguchi, & Anderson, ). This applies also to the lower leg where the close relationship between GSV and SN has been elucidated by previous studies (Dayan, Cura, Cubas, & Carriquiry, ; Murakami, Negishi, Tanaka, Hoshi, & Sezai, ).…”
Section: Introductionsupporting
confidence: 66%
“…5 The vein and the SN are separated by specific connective tissue. 5,29 However, this tissue does not protect the nerve from injuries during iatrogenic maneuvers.…”
Section: Discussionmentioning
confidence: 99%